2012
DOI: 10.1002/emmm.201100190
|View full text |Cite
|
Sign up to set email alerts
|

N‐myc downstream regulated gene 1 modulates Wnt‐β‐catenin signalling and pleiotropically suppresses metastasis

Abstract: Wnt signalling has pivotal roles in tumour progression and metastasis; however, the exact molecular mechanism of Wnt signalling in the metastatic process is as yet poorly defined. Here we demonstrate that the tumour metastasis suppressor gene, NDRG1, interacts with the Wnt receptor, LRP6, followed by blocking of the Wnt signalling, and therefore, orchestrates a cellular network that impairs the metastatic progression of tumour cells. Importantly, restoring NDRG1 expression by a small molecule compound signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
226
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(258 citation statements)
references
References 57 publications
8
226
1
Order By: Relevance
“…It has been reported that the combination of Wnt ligands, LRP6 and ATF3 had a significant inverse correlation with metastasis-free survival of prostate cancer patients 34 . Liu et al…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the combination of Wnt ligands, LRP6 and ATF3 had a significant inverse correlation with metastasis-free survival of prostate cancer patients 34 . Liu et al…”
Section: Discussionmentioning
confidence: 97%
“…This was important to establish, as EGFR is a key regulator of numerous oncogenic downstream signaling pathways (31,43) that were previously found to be inhibited by NDRG1 (4,6,8,(17)(18)(19). Considering the differences between tumors regarding their genetic background, all studies were conducted with both cell lines, to gain insight into NDRG1 function and gauge common functions between cell types.…”
Section: Ndrg1 Down-regulates the Expression Of Egfr In Panc-1mentioning
confidence: 99%
“…In fact, we and others recently demonstrated that NDRG1 can be markedly up-regulated by a novel class of anti-cancer agents, namely the di-2-pyridylketone class of thiosemicarbazones, such as di-2-pyri-dylketone 4,4-dimethyl-3-thiosemicarbazone (Dp44mT) 8 and di-2-pyridylketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC; Fig. 1A) (1,3,18,(21)(22)(23).…”
mentioning
confidence: 98%
See 2 more Smart Citations